Incidence and risk factors of intra uterine fetal death: a retrospective study at a tertiary care centre in Kashmir, India - Ara, Shabnam; Nisar, Shazia; Bashir, Umrazia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Intrauterine fetal death (IUFD) is the tragic event contributing to high perinatal mortality in developing countries. So many risk factors have been seen associated with IUFD that can be prevented with better antenatal care and timely detection at the earliest so that the prevalence can be decreased. This study was done to identify the risk factors associated with IUFD. Methods: This is a retrospective study from done from March 2017 to March 2018 at skims maternity hospital. IUFD was defined as fetal death beyond 20 weeks of gestation. Records were analyzed and data was compiled. Results: In our study there were total of 2500 deliveries out of which 70 were IUFD. Incidence was 28 per 1000 live births. It was found more common in the age group of 20-29 year (65.71%) %). Preeclampsia was the risk factor in 17.14% of cases , followed by abruption in 11.42% followed by placenta previa in 7.14% of cases. However, 20% of the cases had unidentified risk factor. Conclusions: Present study was an effort to compile common risk factors associated with IUFD at tertiary centre of Kashmir.